Influence of Preexisting Cognitive Impairment on Clinical Severity of Ischemic Stroke: The Dijon Stroke Registry. Issue 6 (June 2020) - Béjot, Yannick; Duloquin, Gauthier; Crespy, Valentin; Durier, Jérôme; Garnier, Lucie; Graber, Mathilde; Giroud, Maurice
Abstract : Background and Purpose—: The ongoing ageing population is associated with an increasing number of patients with stroke who have preexisting cognitive impairment. This study aimed to evaluate clinical severity in patients with ischemic stroke according to prestroke cognitive status. Methods—: Patients with ischemic stroke were prospectively identified among residents of Dijon, France using a population-based registry (2013–2017). Prestroke cognitive status (no impairment, mild cognitive impairment [MCI], or dementia) was recorded, and severity at stroke onset was measured using the National Institutes of Health Stroke Scale (NIHSS) score. Association between prestroke cognitive status and severity was evaluated using ordinal regression analysis models in which the NIHSS score was considered as a categorical variable. Results—: Among the 1048 patients (mean age, 76.3±15.2 years; 54.0% women), a greater severity was observed in those with MCI (n=132; median NIHSS: 6; interquartile range, 2–15), and those with dementia (n=164; median NIHSS: 7; interquartile range, 3–16), than in patients without cognitive impairment (n=752; median NIHSS: 3; interquartile range, 1–9). MCI (odds ratio [OR], 1.70 [95% CI, 1.21–2.38]; P =0.002) and dementia (OR, 2.24 [95% CI, 1.65–3.04]; P <0.001) were both associated with a greater severity at onset. The association was still observed after adjustment for clinical variables and proximal arterial occlusion (OR, 1.52 [95% CI, 1.02–2.28]; P =0.04 for MCI; OR, 2.16 [95% CI, 1.45–3.22]; P <0.001 dementia). Further adjustment for prestroke handicap slightly reduced the magnitude of the association (OR, 1.49 [95% CI, 0.98–2.25]; P =0.06 for MCI, and OR, 1.98 [95% CI, 1.26–3.12]; P =0.02 for dementia). The greater severity in patients with prestroke cognitive impairment was not specifically driven by a more severe impairment of either motor or language function. Conclusions—: Patients with preexisting cognitive impairment suffered more severe ischemic stroke. This result could reflect a lower brain tolerance of acute ischemia. Further studies are needed to explore the underlying mechanisms that could be targeted from therapeutic perspectives focusing on neuroprotection.